Feasibility of continuous action unit parameters for road underlay formation - V. A. Nikolaev (Вестник СибАДИ, 2021)
Introduction. Russia has a large spatial disunity of settlements and other objects. Therefore, it is irrational to use low-productivity technical means of cyclical action in the construction of roads. To increase the pace of road construction, improve quality, reduce energy costs for road construction, where relief allows, it is economically feasible to use a set of units of continuous action. Continuous action units, moving one after another, will consistently perform a set of works, carrying out the full construction of the road by flow method. The complex should have a continuous action unit to form a underlying layer. To create complex units, their theoretical justification is necessary. In order to determine the geometric and dynamic parameters of the loading part of the unit to form the underlying layer, the process of moving the bucket filled with soil before it is unloaded is considered.The method of research. Based on the constructive layout of the loading part of the unit, the process of moving the bucket filled with soil before it is unloaded is divided into the stages: vertical ascent, moving in the direction of the leading star of the upper drive, two phases of the bucket rotation on the leading stars of the upper drive, moving from the moment of the end of the turn on the leading star of the upper drive to the start of the turn on the lower turn. When the bucket moves vertically up, the ground is no for dumped. Graphically, this angle of the bucket is chosen when it moves in the direction of the leading star of the upper drive, at which the ground will not fall out of the bucket. Two phases of the bucket rotation on the leading stars of the upper drive and moving the bucket from the moment of the end of the turn on the leading star of the upper drive to the moment of the turn on the lower turning roller are considered. The necessary parameters dependencies have been deduced.Results. Based on the developed methodology, the geometric and dynamic parameters of the loading part of the unit are defined. In particular, the torque of the top drive, the angular velocity of the drive sprockets, the power required for the top drive, the transmission ratio from the hydraulic motor to the sprockets are calculated. Based on the power transferred, a hydromotor was selected for the upper drive of the unit.Conclusion. The calculations reveal the maximum traction force of all buckets during their travel to discharge the soil, the torque of the top drive, the angular velocity of the top drive sprockets and the power required for the top drive. It is advisable to use for the upper drive of the unit gerotor hydromotor MT-160 and two-stage planetary gearbox. The calculations made it possible to develop the design of the elements of the loading part of the continuous action unit to form the underlying layer of roads.